Inhibition of caspases and intracellular free Ca2+ concentrations are involved in resveratrol protection against apoptosis in rat primary neuron cultures - Gong Qi-hai; Wang Qian; Shi Jing-shan; Huang Xie-nan; Liu Qiong; Ma Hu (Acta Pharmacologica Sinica; Vol 28, No 11 (November 2007): Acta Pharmacologica Sinica, 2016)
Aim: To investigate the influence of resveratrol (Res), a nutritional antioxidant, on the inhibition of apoptosis in rat primary neuron cultures. Methods: The cultured cortical neurons of neonatal Sprague-Dawley rats were pretreated with Res (0.1, 1.0, and 10.0 μmol/L) and oxygen-glucose deprivation/reperfusion (OGD/RP) with oxygen and glucose were initiated at d 10 in vitro. Neuronal apoptosis was determined by flow cytometry, and morphological changes of neurons were observed by an electron microscope. For the mechanism studies, the intracellular free calcium concentration ([Ca2+]i) and the transcription of caspases-3 and -12 in neurons were detected by Fura 2/AM loading and real-time RT-PCR, respectively. Results: OGD/RP insult could induce an increase in the apoptotic rate of neurons (from 11.1% to 49.0%), and elicit an obvious morphological change in neurons; pretreatments with Res (0.1, 1.0, and 10.0 μmol/L, respectively) significantly reduced the elevated rate of apoptosis to 41.7%, 40.8%, and 37.4%, respectively, and ameliorated the neuronal morphological injury. Similarly, the OGD/RP insult obviously elicited the elevated levels of the [Ca2+]i and the expressions of caspases-3 and -12 mRNA in neurons. Res pretreatments markedly depressed the neuronal abnormal elevation of [Ca2+]i and the overexpression of caspases-3 and -12 mRNA in a concentration-dependent manner. Conclusion: Res can attenuate the rat cortical neuronal apoptosis induced by OGD/RP. The mechanisms are, at least partly, due to the inhibition of the calcium overload and the overexpression of caspases-3 and -12 mRNA.